PKM MENDORONG PENGELOLAAN DESTINASI WISATA KALI CIMARGA DESA SANGKANMANIK DI TENGAH PANDEMI COVID-19 - Muhammad Saleh; Ismatullah Ismatullah; Deny Aditia; Muhamad Sanan; Veronika Joan Jasmine; Fifa Alifah (Indonesian Collaboration Journal of Community Services, 2021)
This is a village on the border withaimshe village of lewi damar or can be called the end of cimarga lebak-banten sub-district, the problem is still low management about the tourism sector, especially the management of cimarga times located in sangkanmanik.   The tourism sector is one factor that plays a vital role in Indonesia's economic growth and has the second largest foreign exchange contribution in Indonesia after foreign exchange from palm oil exports. Circular issued by the government on March 18, 2020, all activities at home and outdoors in all sectors related to tourism and creative economy were temporarily postponed to reduce the spread of corona. Likewise, the natural tourism sector in Lebak Banten Regency, paralyzed for a while because there are no visitors who come to both local and foreign tourists, thus affecting the local community's income and the Lebak Regency area. The purpose of this community service is to encourage the management of cimarga tourism in the management of tourism in Lebak Regency in the Covid-19 Pandemic and encourage policies that must be prepared by the Government of Lebak Banten Regency so that it can be used as a guideline for stakeholders in the world of tourism in Lebak Banten Regency to jointly realize tourism recovery and be able to bring in large numbers of tourists in the Covid 19 pandemic